STRATEGI DALAM PEMERTAHANAN BAHASA MADURA DI PONDOK PESANTREN SYEKH ABDUL QADIR JAILANI BESUKI - A’ini, Qurratul (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2022)
This study aims to describe the strategy of Islamic boarding schools in maintaining the Madurese language. The object of this research is the Syekh Abdul Qadir Jailani Islamic Boarding School which is located in Belimbing Village, Besuki District, Situbondo Regency. This study is a qualitative descriptive analysis model with primary and secondary data sources. The results of this study indicate several strategies for the Syekh Abdul Qadir Jailani Islamic Boarding School in maintaining the Madurese language, including; 1) Holding Madurese language activities/competitions, 2) Not eliminating Islamic boarding school culture such as reciting Kitab, 3) Familiarizing students with the Madurese language every day. The factors that can influence the Madurese Language Shift are; 1) There is formal education, 2) There are students/teachers from outside the region.